Can electrochemical oxidation techniques really decontaminate saline dyes wastewater?. Issue 3 (September 2015) - Ramjaun, Sadiqua N.; Wang, Zhaohui; Yuan, Ruixia; Liu, Jianshe
Highlights Effect of chloride ions on electrochemical degradation kinetics of dye was examined. MO degradation was significantly enhanced by higher concentrations of chloride. 32 chlorinated organic byproducts of MO were identified by GC–MS method.